Assessment of symptoms, quality of life and associated costs in a one-month follow-up of cancer patients with breakthrough pain: The IMDI Study - Concepción Pérez; Antonio Javier Jiménez-López; Almudena Sanz-Yagüe; Begoña Soler-López (Open Journal of Pain Medicine - Peertechz Publications, 2020)
Purpose: Breakthrough Pain (BTP) observed in up to 66% of cancer patients, is more common in patients with advanced cancer stages and is usually associated with a poor prognosis. The objective of this study was to evaluate the quality of life and control of associated symptoms of cancer patients with breakthrough pain (BTP) after a one-month follow-up in pain and palliative care units and measure the associated cost savings after our intervention. Methods/patients: A one-month observational prospective study was designed. Eight Spanish pain units, eight palliative care units, and one oncology department participated. On baseline and one-month visit, the Edmonton Symptoms Assessment Scale (ESAS), Brief Pain Inventory (BPI) and the quality of life (EORTC QLQ-C30, version 3) were assessed. The direct medical and non-medical costs fixed and variable and the indirect costs of the patient and the caregivers were evaluated and published previously. Factors related to cost and quality of life, were identified using Linear Generalized Models (LGM) type gamma and logistic link. Participants were oncologic patients with BTP, older than 18 years, with controlled background pain. Results: A total of 152 patients with a mean age of 66.8 years (95% CI 64.8-68.8), and 65.8% males were included. All symptoms (ESAS) were significantly improved (p<0.05) from baseline to one month of follow-up. BPI dimensions and all functional and symptoms dimensions of EORTC QLQ-30 were also improved in one month (p<0.01). An improvement in EORTC QLQ-30 global health status-quality of life was associated with a reduction in overall BTP costs. Conclusions: Cancer patients improved their quality of life and cancer associated symptoms in only one month of treatment in pain and palliative care units, and this improvement leads to significant BTP cost savings.